Constraints on the parameters of the neutrino extension of the Standard Model - Volodymyr Gorkavenko; Oleksandr Khasai; Oleg Ruchayskiy; Mariia Tsarenkova (European Physical Journal C: Particles and Fields)
Abstract Heavy neutral leptons (HNLs) are hypothetical particles proposed as a potential explanation for neutrino oscillations and the generation of the baryon asymmetry in the Universe. This paper focuses on HNLs with masses significantly above the electroweak scale. It is challenging to test for the presence of such particles directly. However, they leave behind effective interactions of Standard Model particles, leading in particular to charged lepton flavor violation (cLFV) processes. Non-observation of cLFV processes puts therefore constraints on the parameters of the HNLs. In this paper, we find the relations between the effective operators in the realistic case when neutrino masses are non-zero and the HNLs are non-degenerate. This allows us to strengthen the existing cLFV constraints on the tau-flavors from much stronger constraints on muon and electron flavors. We also link the baryon asymmetry of the Universe to the same higher-dimensional effective operators, providing complementary bounds on these parameters.